Modulation of Late Cretaceous and Cenozoic climate by variable drawdown of atmospheric pCO2 from weathering of basaltic provinces on continents drifting through the equatorial humid belt - Kent, D V; Muttoni, G (Climate of the past, 2013)
The small reservoir of carbon dioxide in the atmosphere (pCO2 ) that modulates climate through the greenhouse effect reflects a delicate balance between large fluxes of sources and sinks. The major long-term source of CO2 is global outgassing from sea-floor spreading, subduction, hotspot activity, and metamorphism; the ultimate sink is through weathering of continental silicates and deposition of carbonates. Most carbon cycle models are driven by changes in the source flux scaled to variable rates of ocean floor production, but ocean floor production may not be distinguishable from being steady since 180 Ma. We evaluate potential changes in sources and sinks of CO2 for the past 120 Ma in a paleogeographic context. Our new calculations show that decarbonation of pelagic sediments by Tethyan subduction contributed only modestly to generally high pCO2 levels from the Late Cretaceous until the early Eocene, and thus shutdown of this CO2 source with the collision of India and Asia at the early Eocene climate optimum at around 50 Ma was inadequate to account for the large and prolonged decrease in pCO2 that eventually allowed the growth of significant Antarctic ice sheets by around 34 Ma. Instead, variation in area of continental basalt terranes in the equatorial humid belt (5° S-5° N) seems to be a dominant factor controlling how much CO2 is retained in the atmosphere via the silicate weathering feedback. The arrival of the highly weatherable Deccan Traps in the equatorial humid belt at around 50 Ma was decisive in initiating the long-term slide to lower atmospheric pCO2 , which was pushed further down by the emplacement of the 30 Ma Ethiopian Traps near the equator and the southerly tectonic extrusion of SE Asia, an arc terrane that presently is estimated to account for 1/4 of CO2 consumption from all basaltic provinces that account for ~1/3 of the total CO2 consumption by continental silicate weathering (Dessert et al., 2003). A negative climate-feedback mechanism that (usually) inhibits the complete collapse of atmospheric pCO2 is the accelerating formation of thick cation-deficient soils that retard chemical weathering of the underlying bedrock. Nevertheless, equatorial climate seems to be relatively insensitive to pCO2 greenhouse forcing and thus with availability of some rejuvenating relief as in arc terranes or thick basaltic provinces, silicate weathering in this venue is not subject to a strong negative feedback, providing an avenue for ice ages. The safety valve that prevents excessive atmospheric pCO2 levels is the triggering of silicate weathering of continental areas and basaltic provinces in the temperate humid belt. Excess organic carbon burial seems to have played a negligible role in atmospheric pCO2 over the Late Cretaceous and Cenozoic.